Archival Context as Archival Authority Record: The ISAAR (CPF) - Thibodeau, Sharon (Archivaria, 1995)
Soon after completing a general standard for description of archival material, known as ISAD(G), the ICA’s Ad Hoc Commission on Descriptive Standards turned its attention to a key related concept: description of the contextual origins of the physical material. Their work is the most recent contribution to a decades long discussion of issues relating to representation of contextual information. The ISAAR (CPF), a draft standard for the compilation of data about persons, families, and organizations that create archival records, is the result of the Commission’s efforts in this area and the subject of this paper. RÉSUMÉ Peu de temps après avoir terminé l’élaboration de critères généraux de description des documents archivistiques connus sous le nom de ISAD (G) la Commission ad hoc des normes de description du Comité international des archives (CIA) a dirigé son attention vers un concept connexe fondamental: la description des origines contextuelles (provenance) des documents. Ce travail constitue la plus récente contribution au débat déjà long d’une décennie au sujet des questions entourant la représentation de l’information contextuelle. ISAAR (CPF) est un ensemble de critères proposés pour la compilation d’informations à propos des personnes, des familles et des organisations créatrices de documents archivistiques et résulte des efforts de la commission dans ce domaine et constitue l’objet du présent article.